The Effect Of Clean Water Product Quality on Customer Satisfaction of Regional Public Water Company Makassar City in Manggala Dictrict - Rofifah.M, Aliyah; Aslinda, Andi; S, Muh Rizal (Pinisi Business Administration Review, 2024)
This study aims to determine how much influence the quality of clean water products has on customer satisfaction at the Makassar City Public Water Company in Manggala District. This study uses a quantitative descriptive type of research with data collection techniques through observation, literature study, interviews, questionnaires, and documentation. The sample used in this study is 100 customers. The data of this study were obtained from the results of data processing using the SPSS 25 application which consisted of validity and reliability tests, descriptive data analysis techniques and inferential analysis. The results of this study indicate that the variables of Clean Water Product Quality and Customer Satisfaction at the Regional Public Water Company of Makassar City in Manggala District have a significant influence. This is evidenced by the results of a simple linear regression test and a correlation coefficient test of 0.662, which means that the relationship between the Quality of Clean Water Products and Customer Satisfaction is strong/high. The coefficient of determination was obtained at 0.438, which means that the effect of Clean Water Product Quality on Customer Satisfaction at the Makassar City Public Water Supply Company in Manggala District obtained a value of 43.8% which was included in the medium category interval.